Application progress of good limb positioning in the rehabilitation of patients with poststroke hemiplegia (脑卒中偏瘫患者康复中良肢位摆放的应用进展) - BIAN Wenjie (边文杰) (中西医结合护理)
Stroke is a common type of cerebrovascular disease, and good limb placement is an important rehabilitation method for patients with poststroke hemiplegia. This paper reviewed studies on importance, application status, influencing factors, intervention timing and procedure of good limb positioning, and provided reference for improving quality of clinical practice and nursing of stroke patients. (脑卒中是临床常见脑血管疾病, 良肢位摆放是目前脑卒中偏瘫患者重要的康复护理措施, 对促进预后具有重要意义。本研究就脑卒中偏瘫患者良肢位摆放的必要性、应用现状、影响因素、干预时机及操作方法进行综述, 旨在为促进良肢位摆放在脑卒中患者中高质量推进和应用提供参考。)